Estimated preventive dose of racemic ketamine for shivering and pruritus prophylaxis in cesarean delivery: a Monte Carlo simulation guided network meta-analysis - Wang, Wei-Long; Zhou, Jin; Cai, Yi; Zheng, Min-Zhu; Chen, Kai-Yu; Hu, Ying; Men, Xin; Sun, Jian-Liang; Qiu, Xu; Zhou, Zhen-Feng (Frontiers in Pharmacology, 2026)
BackgroundThe use of ketamine and esketamine in cesarean delivery is limited by their dose-dependent adverse effects. This study aimed to precisely quantify the dose-response relationships for the prevention of shivering and pruritus and to determine the associated risk of neuropsychiatric side effects, thereby defining its therapeutic window.MethodsA systematic review and network meta-analysis were conducted. We searched databases for randomized controlled trials (RCTs) evaluating a single intravenous bolus of ketamine or esketamine during cesarean delivery under neuraxial anesthesia. Study quality was assessed using the Cochrane RoB 2 tool. We integrated traditional and network meta-analysis with logistic regression, Monte Carlo simulation, and polynomial regression to establish continuous dose-response models and calculate key dose parameters (ED50, ED95).Results25 studies(3,842 participants) were included. The ED50 for preventing pruritus and shivering were 0.122 mg/kg (95% CI, 0.087–0.164) and 0.329 mg/kg (95% CI, 0.260–0.412), respectively. However, at doses of 0.273 mg/kg (ED50) and 0.761 mg/kg (ED95), 50% and 95% of parturients, respectively, experienced subjective side effects.ConclusionThe benefits of low-dose ketamine (≈0.12 mg/kg) for pruritus prophylaxis clearly outweigh its risks. In contrast, the dose required for shivering prevention (≈0.33 mg/kg) falls within the range where side effects become common, resulting in a narrow therapeutic window. This study provides critical dose-finding evidence for individualized, goal-directed use of ketamine in cesarean delivery.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251073122, identifier CRD420251073122.